2021
DOI: 10.1590/1807-1929/agriambi.v25n3p203-208
|View full text |Cite
|
Sign up to set email alerts
|

Quality variables for technological application of cocoa clones from the Brazilian semiarid region

Abstract: Characterization of cocoa clones produced in the semiarid region is necessary to enlarge the database about these implanted clones and thus enhance the quality of their by-products. Therefore, this study aims to evaluate physical, chemical, and physicochemical characteristics of the CCN 51, CEPEC 2004, CEPEC 2005, and PS 1319 clones, produced in the region of Vale do Jaguaribe in the state of Ceará (Brazil), and to suggest food processes or products for them. The clones were evaluated according to their physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…On the other hand, 3003 had the lowest TWF (220.3 g). The data obtained for the weights of fruits were superior to those found by Reges et al (2021), who evaluated clones CCN51, CEPEC 2004, CEPEC 2005, and PS 1319 harvested in an orchard located in the municipality of Russas, State of Ceará, Brazil. However, these authors also observed a great variation in the weights of the fruits, which is related to the specific characteristics of the population studied.…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…On the other hand, 3003 had the lowest TWF (220.3 g). The data obtained for the weights of fruits were superior to those found by Reges et al (2021), who evaluated clones CCN51, CEPEC 2004, CEPEC 2005, and PS 1319 harvested in an orchard located in the municipality of Russas, State of Ceará, Brazil. However, these authors also observed a great variation in the weights of the fruits, which is related to the specific characteristics of the population studied.…”
Section: Resultscontrasting
confidence: 61%
“…They can also be transformed into fuel briquettes, adding value to the product and simultaneously solving the waste disposal problem (Ofori;Akoto, 2020). The shell thickness plays an important role in resistance to Phytophthora palmivora; susceptible cacao fruits have a thinner shell and higher moisture percentage (Reges et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…However, the samples from the 'Ipiranga' variety showed high intensity of fruity flavor and the samples from the 'CCN51' variety presented high intensity of sweet taste and buttery flavor. Brazilian researchers (Reges et al, 2021;Alexandre et al, 2015) reported that the 'CCN51' variety presented higher values to reducing sugar content and soluble solid ( o Brix). Another study carried out with Ecuadorian cocoa varieties found significant difference in the acidity, the 'CCN51' variety was considered the least acid compared to the other varieties studied (Rottiers et al, 2019).…”
Section: Quantitative Descriptive Analysis and Acceptability Of The D...mentioning
confidence: 99%
“…Cacao crops are traditionally planted in regions with annual precipitation ranging between 1500 and 1800 mm [2]. However, the use of irrigation systems and the selection of drought-resistant clones have allowed expanding cacao plantations to drier climates [3,4], with annual rainfall of 800-1000 mm [5].…”
Section: Introductionmentioning
confidence: 99%
“…CCN 51 is a well-recognized cultivar due to its exceptional adaptability to a large range of diferent climates, including semiarid ones, thanks to an advantageous set of traits, which include aspects related to its reproductive phenology (long pollen longevity), physiology (osmotic adjustment, high nonphotochemical quenching, and low Cd accumulation), and high productivity (low pod index) [13]. Tis clone is currently cultivated in Ecuador, Colombia, Perú, and Brasil [5,[14][15][16]. Our fndings allow us to establish the pod's growth curve and predict more accurately the yield of clone CCN 51 when it is cultivated in full sunlight and receiving regular irrigation.…”
Section: Introductionmentioning
confidence: 99%